Fundusze Unii Europejskiej jako wsparcie procesów innowacyjnych polskich przedsiębiorstw - Marciszewska, Anna (The European Funds as Support for Innovation Processes in Polish Enterprises, 2008)
The article discusses the main issues of an innovative process in an enterprise. The author uses accessible information about Polish enterprises. The paper shows the opportunities to enhance the innovative level by using resources from the proper European funds. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 24, s. 159-167